The place of the stored procedures in the cloud databases - Sîrbu, Constantin Florin (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The software as a service model ensures not only cloud applications, but also cloud databases. In this paper we analyze the impact on stored procedures of the switch of the existing application to cloud applications and cloud databases. We demonstrate that the stored procedures and cloud applications have common advantages and we emphasize also other advantages of the stored procedures. As a contribution we propose a list of improvements to stored procedures that can be considered in the new versions of the SQL standard and implemented by the database management systems providers. For the moment the SQL standard does not include any feature related to the cloud databases, so we expect that once again the software industry will be one step forward to the SQL standard.